Fatigue driven matrix crack propagation in laminated composites. (15th May 2018) - Mohammadi, Bijan; Pakdel, Hamed
Abstract: An energy based evolution rule is developed to predict the propagation of mid and outer-ply matrix cracks in laminates with the layups of [0 n / θ m ] s and [ θ m /0 n ] s subject to tensile fatigue loading from initiation up to saturation. A unit cell based variational approach is developed to model the damage state considering both crack density and distribution pattern. Crack densities for different layups are then predicted using only two unit effective material properties which are independent from geometry of laminate. Numerous specimens with 8 different layups are tested and during tensile fatigue loading, matrix cracks multiplication is monitored on site using an appropriate optical microscopy setup. Both material properties of Paris like evolution equation are derived based on experimental observations of crack density in two general layups. Analytically predicted crack densities of tested specimens are shown to be in agreement with experimental observations which confirms empirical parameters to be independent from layup in the tested carbon-epoxy specimens. The independence of the empirical parameters from layup and loading must be validated using extensive experimental results of different layups and materials considering different modes of damage. Graphical Abstract: Highlights: A damage evolution criterion is proposed capable of predicting matrix crack density in laminates under fatigue. The damage evolution criterion contains two empirical parameters which are argued to be independent from laminate layup and loading. Independence of the empirical parameters from layup and loading is investigated in carbon-epoxy laminates with two general layups.